Beneficiaries of conflict: a qualitative study of people’s trust in the private health care system in Mogadishu, Somalia - Gele AA; Ahmed MY; Kour P; Moallim SA; Salad AM; Kumar B (Dove Medical Press, 2017)
Abdi A Gele,1–3 Mohamed Yusuf Ahmed,4 Prabhjot Kour,2 Sadiyo Ali Moallim,5 Abdulwahab Moallim Salad,3 Bernadette Kumar2 1Institute of Nursing and Health Promotion, Department of Health, Oslo and Akershus University College of Applied Science, 2Department for Research, Norwegian Centre for Minority Health Research, Oslo, Norway; 3Center for Health Research, Somali National University, 4Department of Business Management, Simad University, 5Faculty of Medicine, Benadir University, Mogadishu, Somalia Background: In 2005, the World Health Conference called for all nations to move toward universal health coverage, which is defined as “access to adequate health care for all at an affordable price”. Despite this, an estimated 90% of Somalia’s largely impoverished population use private health care. Therefore, considering that the private health care system is the dominant health care system in Mogadishu, Somalia, exploring the accessibility to, as well as people’s trust in, the private sector is essential to help contribute an equitable and affordable health care system in the country.Methods: A qualitative study using unstructured interviews was conducted in Mogadishu from August to November of 2016. A purposive sampling approach was used to recruit 23 participants, including seven medical doctors who own private health centers, eight patients, five medical students and three senior officials who work for the Ministry of Health. Data were analyzed using a thematic analysis.Results: Our findings show that the private health care system in Mogadishu is not only unregulated but also expensive, with the cost of health care often unaffordable for the majority of the country’s citizens. There is evidence of prescription of inappropriate treatment, tendency to conduct unnecessary laboratory tests, excessive use of higher diagnostic technologies and overcharging – including the widespread practice of further appointments for follow-up – which inflates the costs. The study also found poor patient–provider relationship and widespread distrust of the private health care system.Conclusion: The study findings underline the need for the Somali government to develop regulatory mechanisms and guidelines with the potential to guide the private health care sector to provide equitable and affordable health care to people in Mogadishu. The doctor–patient relationship has been – and remains – a keystone of care; thus, there is an urgent need for guidelines for private health care providers to treat their patients with dignity and respect. The education system, particularly the syllabus used by medical faculties, should be reviewed and improved to provide medical students with necessary knowledge, skills and attitudes to maintain patient dignity and rights. Keywords: Somalia, private health care, user fees, dignified care